4CPS-110 Association between baseline characteristics and first-line chemotherapy in advanced gastric cancer patients. Issue 1 (23rd March 2023) - Arias, A; Alvarez Manceñído, FJ; Martinez Torron, A; Macia Rivas, L; Calvo, A; Visa, L; Limón, ML; Iglesias Álvarez, G; Mariño Méndez, A; Pimentel, P; Lozano-Blázquez, A
Abstract : Background and Importance: There is no standard first-line regimen for HER2-negative advanced gastroesophageal adenocarcinoma. Aim and Objectives: To study the variability in the choice of regimens according to tumour, patient baseline variables and prescribing physician. Material and Methods: Patients with HER2-negative advanced gastroesophageal adenocarcinoma diagnosed between 2008 and 2021 from a multicentre registry (34 centres) were included. Patients received chemotherapy based on platinum (cisplatin or oxaliplatin) and fluoropyrimidine (5-fluorouracil or capecitabine). Association between the following baseline variables: specialty of the prescribing oncologist, ECOG-PS (Eastern Cooperative Oncologic Group Performance Status), serum albumin, tumour location, Lauren classification and platinum and fluoropyrimidine regimens were evaluated and Chi 2 test was performed. Results: A total of 1334 patients were registered, 66.49% (n=893) were male. Seventy percent of our population was treated almost equally with FOLFOX6 (n=468) and XELOX (n= 466), followed by XP 19% (n=252), FP3w 7% (n=95) and in fewer percent with FUOX modified 3%(n=44), FP4w 1% (n=12) and FLO (n=6). Oxaliplatin was the most commonly used platinum (73%, p=971) while both fluoropyrimidines where administered in a similar proportion (capecitabine 54%). Patients were mainly treated by an oncologist specialising in gastric cancer (95%). General oncologist preferred oxaliplatin-based regimens (46% vs 6%) and specialist opted more for cisplatin and capecitabine associated regimens (p=0.031). Patients with worst performance status (ECOG=2) were treated to a greater extent than the overall population with schemes based on oxaliplatin and 5-fluorouracil 50% versus 38% of the general population. Those with ECOG=0 received more than expected schemes with cisplatin and capecitabine (21%, n=55).Patients with baseline hypoalbuminaemia (albumin < 35 g/dL) received intravenous fluoropyrimidine schedules with both oxaliplatin (47%, n=156) and cisplatin (9%, n=3) in a higher proportion than expected (p<0.000).According to Lauren`s classification, there was a higher use of capecitabine versus 5-FU in intestinal tumours. This trend is reversed in diffuse tumours (p<0.000). Conclusion and Relevance: In this study we found an association between the platinum and fluoropyrimidine selected in patients with advanced gastric cancer and certain baseline variables. Future studies are needed to evaluate whether this choice has an impact on patient benefit. References and/or Acknowledgements: 1. This study is part of a doctoral thesis of the Doctoral Programme in Pharmacy of the University of Granada. Thanks for your support in this research. Conflict of Interest: No conflict of interest